1995
DOI: 10.1177/0310057x9502300207
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing Venepuncture Pain: Comparison of Lignocaine Injection, Butterfly (21 Gauge and 23 Gauge) and Venflon (20 Gauge)

Abstract: Two hundred and seventy-eight patients scheduled for all types of surgery and premedicated with diazepam and metoclopramide were randomly allocated to one of four groups to compare the relative pain of an injection of 0.25 ml of lignocaine 1% via a 25 gauge needle with the pain of the siting of a 21 gauge Butterfly (Abbott), 23 gauge Butterfly or a 20 gauge Venflon (Vigo Spectramed). The injection of lignocaine and insertion of the 23 gauge Butterfly were associated with the least complaints of pain and least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Previous studies have found a complex relation between sex and pain, some suggesting a diVerence with men reporting less pain, others have contradicted this and some have found no diVerences. 4 17 18 Our study found the mean pain scores for men and for women were not significantly diVerent, and there was no correlation with age. One explanation for this might be that the way we express pain is culturally dependent and varies with age and sex even though the level of pain perceived is constant.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have found a complex relation between sex and pain, some suggesting a diVerence with men reporting less pain, others have contradicted this and some have found no diVerences. 4 17 18 Our study found the mean pain scores for men and for women were not significantly diVerent, and there was no correlation with age. One explanation for this might be that the way we express pain is culturally dependent and varies with age and sex even though the level of pain perceived is constant.…”
Section: Discussionmentioning
confidence: 68%
“…Venipuncture pain is effectively reduced by 1% lignocaine infiltration [17,18], which in itself causes only minimal discomfort. Venipuncture pain is effectively reduced by 1% lignocaine infiltration [17,18], which in itself causes only minimal discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…A perplexing finding in this study was the lack of effectiveness of lignocaine infiltration compared with placebo. Venipuncture pain is effectively reduced by 1% lignocaine infiltration [17,18], which in itself causes only minimal discomfort. The explanation of this discrepancy between spinal puncture and venipuncture may be twofold, the different solution and the different injection site.…”
Section: Discussionmentioning
confidence: 99%